A Comparison of Two Methods for Solving Electromagnetic Field Integral Equation. (2nd July 2011) - Jebli, L.
Abstract : The present paper aims to compare Harrington's direct method of moment (MoM) with the conjugate gradient method (CGM) by evaluating the total current solving the electric field integral equation (EFIE). Based on their performances, the number of iterations needed for convergence, storage, and the level of precision, it is found that the direct MoM is more efficient than other iterative CGM.